Heartbreak and Despair: An analysis of Kierkegaard's applicability to secular existential analysis: Winning entry to the SEA/Existential Analysis Writing Award on Kierkegaardian Contributions to Existential Therapy (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Kierkegaard's model of despair and its resolution in faith has parallels with how the existential analyst approaches a client who is avoiding awareness of ultimate concerns. This pertains particularly to clients whose romantic heartbreak masks a deeper existential concern.
Keywords: Kierkegaard; Anti-Climacus; Yalom; ultimate concern; heartbreak; despair